The Digraph اى in the Quranic Consonantal Text and the Identification of a New Letter Shape for Final Hē in the 7th to 8th Century Arabic Script - Ahmad Al-Jallad (Columbia University Libraries, 2021)
This paper proposes a hitherto unrecognized orthographic practice in the Quranic consonantal text: use of the digraph اى ,that is, alif + denticle, to represent the noninitial glottal stop, most often adjacent to the high vowels i/ī and less commonly in other environments. This feature leads to the identification of a new letter shape for the final hē in the early Islamic Arabic hand, originating in the Nabataeo-Arabic script, which in turn can explain a number of previously enigmatic spellings in the Quranic consonantal text.